Gender‐specific outcomes after percutaneous left atrial appendage closure: A nationwide readmission database analysis. (20th January 2022) - Patel, Neel; Ranka, Sagar; Hajra, Adrija; Bandyopadhyay, Dhrubajyoti; Amgai, Birendra; Chakraborty, Sandipan; Khalid, Mazin; Goyal, Amandeep; Dalia, Tarun; Reddy, Yeruva Madhu; Shani, Jacob
Abstract: Introduction: Thromboembolism‐associated stroke is the most feared complication of atrial fibrillation (AF). Percutaneous left atrial appendage closure (pLAAC) is indicated for stroke prevention in patients with AF who can not tolerate long‐term anticoagulation. We aim to study gender differences in peri‐procedural and readmissions outcomes in pLAAC patients. Methods: Using the national readmission database from January 2016 to December 2018, AF patients undergoing the pLAAC procedure were identified. We used multivariate logistic regression analyses and time‐to‐event Cox regression analyses to conduct the study. Propensity matching with the Greedy method was done for the accuracy of results. Result: A total of 28 819 patients were included in our study. Among them 11 946 (41.5%) were women and 16 873 (58.6%) were men. The mean age of overall population was 76.1 ± 8.5 years, with women ~1 year older than men. The overall rate of complications was higher in women (8.6% vs. 6.6%, p  < .001), primarily driven by bleeding‐related complications, that is, major bleed (odds ratio [OR]: 1.32 95% confidence interval [CI]: 1.03–1.69, p  = .029), blood transfusion (OR: 1.45, 95% CI: 1.06–1.97, p  = .019), and cardiac tamponade (OR: 1.80, 95% CI: 1.13–2.89, p  = .014). Women had two times higher peri‐procedural ischemic stroke. There was no difference in peri‐procedural mortality. Women remained at 20% and 13% higher risk for readmission at 30 days and 6 months of discharge. Conclusion: Women had higher peri‐procedural complications and were at higher risk of readmissions at 30 days and 6 months. However, there was no difference in mortality during the index hospitalization. Further studies are necessary to determine causality.